Talking it out? Metacognition, teacher talk, and comprehension consequences - Jennie Baumann (Language and Literacy: A Canadian Educational e-journal)
This study examines how the amount of teacher talk supports elementary-aged readers’ use of metacognitive strategies to comprehend text. One fourth-grade teacher’s small group reading sessions (n=5 sessions; 2 with advanced readers, 3 with striving readers) were observed and analyzed for metacognitive reading strategy implementation, some with a think-aloud protocol and some with curriculum materials. Results indicate that more teacher talk during small group lessons led to fewer metacognitive behaviors from striving readers. Small-group lesson talk focused on lower-level questions and problem-solving/support strategies initiated and scaffolded by the teacher, resulting in minimal opportunities for students to independently engage with text.